Efficacy of Stentless Aortic Bioprosthesis Implantation for Aortic Stenosis with Small Aortic Annulus - Murashita, Takashi; Okada, Yukikatsu; Kanemitsu, Hideo; Fukunaga, Naoto; Konishi, Yasunobu; Nakamura, Ken; Koyama, Tadaaki (The Thoracic and Cardiovascular Surgeon, 2015)
Background In patients with small aortic annulus, sufficient size of stented aortic bioprosthesis cannot be implanted without additional procedures. In such cases, we use stentless aortic bioprosthesis to obtain sufficient effective orifice area. In this study, we investigated long-term impact of stentless aortic bioprosthesis on clinical outcomes, compared with stented aortic bioprosthesis.Materials and Methods We retrospectively investigated 140 patients who underwent aortic valve replacement (AVR) with porcine bioprosthesis for severe aortic stenosis between 1999 and 2010. Patients who had moderate or more aortic regurgitation and who underwent concomitant mitral procedures were excluded. A total of 69 patients (49%) were implanted stentless bioprosthesis (Freestyle group; Medtronic Inc, Minneapolis, Minnesota, United States) and 71 patients (51%) were implanted stented bioprosthesis (Mosaic group; Medtronic Inc). Follow-up was complete in 97.9% patients. Median follow-up period was 4.2 years.Results Patients in Freestyle group had smaller body surface area, smaller aortic annulus diameter, smaller aortic valve area, larger mean pressure gradient, higher peak velocity across aortic valve, larger left ventricular mass index (LVMI), and lower left ventricular ejection fraction (LVEF). Mean size of implanted prosthesis was larger in Freestyle group. In-hospital mortality was 1.4% in Freestyle group and 2.8% in Mosaic group (p = 0.980). Five-year survival rate was not different between two groups (5-year survival rate was 87.5 ± 4.7% in Freestyle group and 84.1 ± 7.5% in Mosaic group; log rank, p = 0.619). Late New York Heart Association functional class was lower in Freestyle group. Late LVMI and LVEF became similar between two groups.Conclusion Stentless aortic bioprosthesis is superior in left ventricular remodeling after AVR for aortic stenosis and is especially effective for small aortic annulus.
Keywords: aortic valve and root; heart valve surgery; clinical outcomes